Fantasy Sports: Socialization and Gender Relations. (February 2015) - Howie, Luke; Campbell, Perri
Fantasy sports are played by millions of people throughout the world. By 2017, it is predicted to be an industry with a turnover measured in billions of dollars. Recent scholarly attention has focused on the motivations for participating in fantasy sports leagues. In this article, we report on ongoing qualitative research being conducted with fantasy sports enthusiasts and their wives and partners in Australia. There has been little previous research into the attitudes of wives and partners toward the fantasy sports habits of enthusiasts. The enthusiasts studied here play in a long-running fantasy National Basketball Association (NBA) league that began in 1999 and continues in a relatively unchanged format. We argue that social factors are the primary motivation for participants in this league in terms of enhancing and maintaining existing friendships. How those social factors are practiced, however, has significant consequences for managing workplace and relationship demands.